the Uric Acid Levels Are Lowered by Traditional Boiling Water from Leaves at Elderly Posyandu Jonggon Jaya Kutai Kartanegara - Hidayat, Faried Rahman; Rahman, Hidayat Faried; Nikki, Ardilla; Siti, Asyah; Hudayati, Hudayati (Jurnal Ilmu Kesehatan, 2023)
Purpose of study: To know that there are some benefits of some leaves (bay leaves, soursop leaves and celery leaves) which are boiled and then drunk every day to reduce uric acid levels in the body. Methodology: Quasi-Experimental Design which was carried out by Pretest–Posttest Control Group Design. The number of samples was 90 people, namely 15 people in the intervention group with boiled bay leaves, 15 people in the intervention group with boiled soursop leaves, 15 people in the intervention group with boiled celery leaves and 15 people as controls in each treatment. Data collection uses observation with the new GCU tool. Univariate and bivariate analysis with the tests used were the Paired T Test. Results: Based on the test results obtained the effect of traditional boiled water of bay leaves, soursop leaves and celery leaves to reduce uric acid levels in the blood (P value: 0.000) so that it can be stated that H0 is rejected and HA is accepted which can be said to have the effect of boiling bay leaves, soursop leaves and celery leaves on decreasing uric acid levels in the elderly Applications: Traditional boiled water of bay leaves, soursop leaves and celery leaves can be drunk to help reduce blood uric acid levels in the elderly Posyandu Jonggon Jaya Kutai Kartanegara.